Cultural and Moral Values in Cinderella and Bawang Merah Bawang Putih - Budiman, Muhammad Arief; Khudlori, Amin (Indonesian Research Journal on Education, 2025)
Children’s literature plays a crucial role in shaping moral values and reflecting cultural norms. Although many studies have examined individual folktales, limited research directly compares Western and Eastern narratives to understand how cultural contexts shape moral instruction. This study compares the Western folktale Cinderella and the Eastern folktale Bawang Merah Bawang Putih to examine how each story teaches ethics and virtues to children. Using a qualitative comparative analysis, data were collected through textual analysis and a review of relevant literature. Results show that Cinderella emphasizes individual virtue rewarded through external assistance, reflecting Western ideals of personal achievement, while Bawang Merah Bawang Putih highlights moral integrity and the consequences of actions, reflecting Eastern values of communal harmony. By offering a cross-cultural comparison, this study contributes to a deeper understanding of how folktales function as culturally embedded tools for moral education and provides insights for educators and researchers on integrating cultural narratives into ethical instruction.